Effect of Carbamide on the Weight of 1000 Grains of Varieties of Winter Soft Wheat While Feeding Through the Leaves in the Full Earning Phase - R.Z. Khasanova; A.O. Aripov (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
Enhancing wheat productivity and grain quality is a strategic agricultural goal, particularly under conditions of increasing population pressure, soil degradation, and climate variability. Winter soft wheat varieties, especially during the reproductive development phase, require additional nutrient inputs beyond what root systems can supply. Foliar application of nutrients like urea during the full heading (earing) phase has emerged as a cost-effective agronomic solution. Although foliar feeding is acknowledged for its efficiency, there remains a lack of consensus on the optimal application rates, particularly under irrigated conditions and across different wheat varieties.This study aimed to assess the effect of foliar-applied urea at different rates on the 1000-grain weight of Yaksart and Gazgan winter wheat varieties. Field experiments conducted from 2015 to 2017 revealed that a 40 kg/ha urea solution applied through foliar feeding during the full heading phase resulted in the highest increase in 1000-grain weight—up to 2.8 g in Yaksart and 2.7 g in Gazgan—compared to control groups. Lower or higher dosages (30 and 50 kg/ha) were comparatively less effective. The findings identify a precise and optimal rate of urea application for enhancing grain weight during a critical growth phase, based on multi-year, replicated trials under local agro-climatic conditions. This study provides actionable recommendations for wheat farmers to improve grain yield quality via targeted foliar nutrition. Future research may explore the physiological mechanisms involved and test scalability under diverse soil types and climatic zones.